A study of the effectiveness of school health education programs on selected mosquito borne diseases: school based cross-sectional study - Sureshbabu, Jayanthi; Vasudevan, Senthilvel; Raj, Priyanka (International Journal of Research in Medical Sciences, 2017)
Background: School health education programs provide a convenient platform for engaging the students in health promotion activities. Public health problems like mosquito borne diseases cannot be controlled without active participation of the community and students are a resourceful component of the community who can be encouraged to take up activities to control mosquito borne diseases in the community. Methods: School-based cross-sectional study was conducted in December 2010 to March 2011 among 508 school students selected at random from students studying in the eighth to tenth standard. P < 0.05 was considered as statistically significant. Results: Totally 508 students were included in this study. The number of students unaware of the stages in the mosquito life cycle and the mosquito’s resting habits reduced from 420 (82.68%) to 19 (3.74%) and 103 (20.28%) to 13 (2.56%) respectively. The number of students with correct knowledge of the biting habits of the female mosquito and personal protection (PP) measures increased from 31.69% to 97.05% with statistically highly significant (p <0.0001) and 52.95% to 74.21% respectively. Conclusions: The present study suggested that the school health education program is effective in creating awareness and increasing the knowledge regarding mosquito borne diseases among school children and possibilities of successfully engaging the community at large in the fight against mosquito borne diseases. The need would be to sustain this activity and implement it in schools as part of the vector borne disease control programme.